2007
DOI: 10.1016/j.molbiopara.2007.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Are Caenorhabditis elegans receptors useful targets for drug discovery: Pharmacological comparison of tyramine receptors with high identity from C. elegans (TYRA-2) and Brugia malayi (Bm4)

Abstract: The biogenic amine, tyramine (TA), modulates a number of key processes in nematodes and a number of TA-specific receptors have been identified. In the present study we have identified a putative TA receptor (Bm4) in the recently completed Brugia malayi genome and compared its pharmacology to its putative C. elegans orthologue, TYRA-2, under identical expression and assay conditions. TYRA-2 and Bm4 are the most closely related C. elegans and B. malayi BA receptors and differ by only 14 aa in the TM regions dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This receptor modulates a number of key processes in nematodes, including pharyngeal pumping, locomotion and egg laying (SMITH et al, 2007), besides being expressed in all phases of the life cycle of H. contortus (RAO et al, 2010), justifying the possible interaction of this monoterpene with SER-2 tyramine receptor and its larvicidal action. Both thymol and TA showed larvicidal action indicating that replacement of the hydroxyl radical by the acetyl group did not change the larvicidal activity of TA, proving that the action of thymol is not related to the hydroxyl radical.…”
Section: Discussionmentioning
confidence: 99%
“…This receptor modulates a number of key processes in nematodes, including pharyngeal pumping, locomotion and egg laying (SMITH et al, 2007), besides being expressed in all phases of the life cycle of H. contortus (RAO et al, 2010), justifying the possible interaction of this monoterpene with SER-2 tyramine receptor and its larvicidal action. Both thymol and TA showed larvicidal action indicating that replacement of the hydroxyl radical by the acetyl group did not change the larvicidal activity of TA, proving that the action of thymol is not related to the hydroxyl radical.…”
Section: Discussionmentioning
confidence: 99%
“…BLAST analysis against the NCBI non-redundant protein database (nr) revealed that CgGPR1 shows the most significant sequence identity with characterized LymOAR2 (42%) [22], the Caenorhabditis elegans TA receptor TYRA2 (32%) [36], and the Brugia malayi TA receptor Bm4 (29%) [37], suggesting that CgGPR1 is likely to be a biogenic amine receptor.…”
Section: Resultsmentioning
confidence: 99%
“…elegans TYRA2 [36] and B . malayi Bm4 [37]. Among these, CgGPR1 was phylogenetically most closely related to L .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these molecules act at GPCRs (Komuniecki et al, 2004), though, as stated earlier, nematodes also possess chloride channels gated by 5-HT, dopamine and tyramine. At least some of these receptors have also been identified in parasitic species (Huang et al, 1999(Huang et al, , 2002Smith et al, 2003Smith et al, , 2007 and many have distinct pharmacological characteristics that suggest that nematode-specific agonists and antagonists could be developed as useful anthelmintics (White et al, 2007). In C. elegans, dopamine and 5-HT have well-established roles in modulating behavior, including locomotion, feeding and egg-laying (Chase and Koelle, 2007).…”
Section: G Protein-coupled Receptorsmentioning
confidence: 99%